Study on the mechanical properties and microstructure of PVA fiber-reinforced waste glass powder concrete - Yi Zhao; Siwen Chen; Shuisheng Yu; Shuai Wu; Yijie Bao (AIP Advances)
The recycling of waste glass as an auxiliary cementitious material in concrete is a sustainable solution. However, it introduces a challenge in terms of the toughness of the resultant concrete. To address this, the present study investigated the enhancement of toughness in waste glass powder concrete through the incorporation of polyvinyl alcohol (PVA) fibers. The research assesses the compressive strength and splitting tensile strength of concrete samples containing waste glass powder and PVA fibers that were cured for 7 and 28 days, respectively. In addition, the microstructural characteristics and interfacial transition zones of the concrete were examined by scanning electron microscopy and energy-dispersive spectroscopy. These findings indicate that the integration of PVA fibers effectively mitigates the strength reduction in waste glass powder concrete. The optimal fiber concentration was identified as 1%, transitioning the failure mode of the concrete from brittle to ductile. The presence of PVA fibers does not alter the element type at the aggregate–cement matrix interface but influences the element content. The –C–OH groups in PVA fibers form hydrogen bonds with –OH groups in cement hydration products, aided by the non-circular cross section and molecular structure of the fibers, enhancing adhesion at the cement matrix interface. An appropriate amount of PVA fibers increases the Ca/Si ratio in waste glass powder concrete, reducing C–S–H production at the interfacial bond and thereby improving the internal structure of the concrete. However, excessive PVA fiber content diminishes these benefits.